(untitled) (Research, Society and Development, 2022)
Objective: To identify, in the literature, the challenges faced by health professionals when working in a multidisciplinary team of palliative care. Methods: This is an integrative review, carried out through searches in the Latin American and Caribbean Literature on Health Sciences, Medical Literature Analysis and Retrieval System Online and Scientific Electronic Library Online databases, during the month of November, 2021. Results: After the searches, 78 studies were found. Of these, 20 were included because they met the purpose of the study and proposed criteria. Such research analyzed different professional categories, with emphasis on nurses and doctors, followed by physiotherapists, nutritionists, nursing technicians, psychologists, occupational therapists and pharmacists. Among the challenges investigated, there is a lack of professional training and communication problems within the multidisciplinary team. In addition, the most pointed challenge was the lack of standardization of protocols for indicating and conducting palliative care, as well as the need for a better structure for reception and communication with family members. Conclusion: Therefore, the results found demonstrate that the professionals of the multidisciplinary team in palliative care face challenges related to aspects such as: professional training/qualification and operationalization of the teamwork routine; the field of action and the deficient support network for the patient; and communication/reception to patients and family members. This evidence demonstrates the need to improve professional qualification in palliative care. Thus, the dissemination of knowledge about palliative care can contribute to preventing or mitigating the challenges that may arise during professional practice.